Implementing Sentiment Analysis of Online Reviews to Improve Product and Customer Satisfaction: A QFD / Kano Model Integration - Mohasseb, Ayman Mohamed Ameen (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
This study developed a quality function deployment (QFD) / KANO model integration method for improving product development in terms of customer satisfaction by utilizing sentiment analysis as a natural language processing (NLP) technique based on online reviews. this method is an alternative to traditional methods that rely on questionnaires and interviews to reduce costs and accelerate development. instead of employing the QFD and KANO models independently, the integration technique produces findings almost immediately, utilizes thousands of evaluations and opinions at a cheap cost, and aids with decision-making issues. the data for this study were gathered from amazon's enormous review database. amazon dataset with 400,000 product ratings of smartphone from June 2014 to December 2022 were used. the merging of two models has created new opportunities for smartphone manufacturers in terms of deciding which technical specifications need to be modified and improved with customer satisfaction in mind. this could encourage companies to gradually heading towards the current approach that this research introduces, which makes it easier to gather feedback from a variety of customers in an affordable way. طورت هذه الدراسة طريقة دمج نموذج كانو / نشر وظيفة الجودة QFD) / Kano model) لتحسين تطوير المنتج بالنظر إلى رضا العملاء من خلال استخدام تحليل الآراء sentiment analysis كتقنية لمعالجة اللغة الطبيعية (NLP) تعتمد على المراجعات عبر الإنترنت. تعد هذه الطريقة بديلا للطرق التقليدية التي تعتمد على الاستبيانات والمقابلات بهدف تقليل التكاليف وتسريع التطوير. بدلا من استخدام نموذجي كانو ونشر وظيفة الجودة بشكل مستقل، تنتج هذه التقنية نتائج فورية تقريبا، وتستخدم آلاف التقييمات والآراء بتكلفة رخيصة، وتساعد في قضايا اتخاذ القرار. تم جمع البيانات لهذه الدراسة من قاعدة بيانات المراجعات الضخمة لشركة Amazon. تم استخدام مجموعة بيانات Amazon التي تحتوي على ٤۰۰۰۰۰ تقييم لمنتج الهواتف الذكية من يونيو ۲۰۱٤ إلى ديسمبر ۲۰۲۲. أدى دمج النموذجين إلى خلق فرص جديدة لمصنعي الهواتف الذكية من حيث تحديد المواصفات الفنية التي تحتاج إلى تعديل وتحسين مع وضع رضا العملاء في الاعتبار. وقد يشجع هذا الشركات على التوجه تدريجيا نحو الطريقة الحالية التي يقدمها هذا البحث، والتي تجعل من السهل جمع الملاحظات من مجموعة متنوعة من العملاء بطريقة منخفضة التكلفة.